Fine needle aspiration in the diagnosis and classification of hepatoblastoma: Analysis of 21 New Cases. Issue 2 (9th December 2016) - Vlajnic, Tatjana; Brisse, Hervé J.; Aerts, Isabelle; Fréneaux, Paul; Cellier, Cécile; Fabre, Monique; Klijanienko, Jerzy
Abstract : Background: Diagnosis of hepatoblastoma (HBL) is based on characteristic clinical and radiological presentation, young age and marked elevation of serum α‐fetoprotein (aFP). Fine needle aspiration (FNA) technique is successfully used in the diagnosis of hepatoblastoma. To evaluate the value of FNA in the diagnosis and subtyping of HBL, we report our experience correlated to histological sections (core needle biopsy, CNB). Methods: From 1991 to 2015, 21 cases from 20 patients were cytologically diagnosed as HBL. The patients were 15 males and 5 females, mean age being 3 years, and median age being 2 years and 4 months. Serum aFP levels ranged from negative to 1, 285, 000 ng/ml. We defined cytological criteria to diagnose fetal, embryonal, mesenchymal, and small cell undifferentiated components. Results: The accurate cytological diagnosis of HBL was made in all cases; 8 cases exhibited a single component and 13 cases exhibited two or more components. Fetal and embryonal components were seen in 18 and 13 cases, respectively, and small cell undifferentiated component was seen in one case. Mesenchymal component was seen in 12 cases. Comparing cytology and histology, identical components were identified on both, FNA and CNB in 14 cases. When analyzing only the presence of epithelial components, 17 cases were concordant in both techniques. Conclusion: FNA allows to accurately diagnose HBL and recognize its histological subtypes. On the basis of high concordance between cytological and histological diagnosis, FNA is validated as an alternative diagnostic method to CNB. Diagn. Cytopathol. 2017;45:91–100. © 2016 Wiley Periodicals, Inc.